Fungal degradation of lignin-based rigid polyurethane foams - Amaral, Joana S. (2014)
In this work, the ability of Aspergillus niger to degrade two lignin-based rigid polyurethane (RPU) foams was evaluated and compared with a control RPU foam based on a commercial polyether-polyol, Lupranol 3323. The foams degradation was studied according to different procedures, namely by setting different series of batch cultures, either using liquid media or soil conditions, for 90 days at 30 C. For the soil conditions, two different assays were performed, namely with and without A. niger addition. The changes in the morphology of the RPU foams were evaluated by optical (OM) and scanning electron microscopy (SEM), whereas the structural modifications were inspected by FTIR spectroscopy. After 90 days treatment, morphological changes were clearly visible at the surface (cell wall) of the two lignin-based foams indicating a stronger effect of the microorganisms’ activity in these samples. FTIR spectra confirmed that the chemical structure of the polymer suffered modifications after the respirometry assays due to microorganisms attack. Comparatively to the commercial foam, it was observed that both the lignin-based foams presented a higher degradation level.